The Utilization of Online Games to Enhance Students’ Vocabulary Mastery in Senior High School - Aulia, Rafida Putri; Laksana, Kusuma Nata; Maulida, Sarah; Rahman, Faizahani Ab; Apoko, Tri Wintolo (Journal of Languages and Language Teaching, 2024)
Language learning, particularly vocabulary development, is crucial in mastering English as a foreign language. However, teaching vocabulary effectively can be challenging, and traditional methods like memorization may not always be engaging for students. The study aims to explore the impact of using popular online games, such as Mobile Legends, PUBG Mobile, League of Legends, and Minecraft on students' vocabulary mastery. A qualitative research design was employed, involving structured interviews and focus group discussions with eight students from a senior high school in Jakarta. The findings revealed that online games provided an immersive and enjoyable environment for vocabulary enrichment, offering both direct and indirect opportunities to encounter new words and phrases. The study demonstrated that online games could positively influence students' motivation and interest in learning English vocabulary, resulting in improvements in their language skills. It is then suggested that students should practice using English by utilizing online games relevant to the promotion of their English vocabulary mastery.